Ethnobotanical survey of anti-infective plants used by traditional healers in Brazzaville, Republic of Congo - Muanga, Claude-Josué K.; Luzala, Miryam M.; Landamambou, Arland; Kyana, Joseph; Mayuwu, Merveille K.; Kambale, Espoir K.; Memvanga, Patrick B. (Orapuh Journal, 2024)
Introduction Infectious diseases are a real public health problem. Faced with the problem of antimicrobial resistance (AMR) in their treatments, it is essential to find alternative solutions. Purpose The present study aimed to gather more information about medicinal plants used to treat infectious diseases by traditional healers in two markets of Brazzaville City, in the Republic of Congo. Methods This ethnobotanical survey was carried out through individual interviews in the local language, using a semi-structured questionnaire. Results From August 24 to September 02, 2022, fifteen traditional healers were enrolled, 7 men and 8 women. The average age of respondents was 47 years old. The literacy level was 60%. Most of the traditional healers belonged to the Lari ethnic group. Their knowledge of plant use was largely derived from cultural heritage. Twenty-three plant species were identified. These were Acacia nilotica, Chenopodium ambrosioides, Cyathula prostrata, Caladium bicolor, Hua gabonii, Aframomum stipulatum, Annona arenaria, Acanthus montanus, Asystasia gangetica, Alchornea floribunda, Milletia congolensis, Mangifera indica, Phaulopsis poggei, Anthonotha macrophylla, Dichrostachys glomerata, Heinsia crinita, Alstonia congensis, Acanthus montanus, Rauvolfia obscura, and Carica papaya. The most represented family was Acanthaceae (17.39%). Carica papaya (18.96%) was the most frequently cited species for the treatment of infections. The leaves represented the plant parts most used by the respondents (26.02%). Decoction (48%) was the preparation technique most frequently used to facilitate drug administration. The oral route was the most widely used (52%). Malaria and gonorrhea (22.8%) topped the list of infections treated by the traditional healers. Conclusion These findings illustrate the wealth of indigenous knowledge of plants with anti-infectious properties in the Congolese flora. They also highlight the potential of traditional medicine plants as sources of new antimicrobial agents, which could play an essential role in combating antimicrobial resistance.